Anorexia nervosa in association with diabetes mellitus--a cognitive-behavioural approach to treatment. - Peveler, R; Fairburn, C (1989)
A case of anorexia nervosa occurring in a patient with diabetes mellitus is reported. The patient was successfully managed using a cognitive-behavioural treatment approach. The presence of diabetes necessitated certain modifications to the standard cognitive-behavioural treatment for anorexia nervosa, including self-monitoring of diabetic regimen behaviours, attention to the adequacy of glycaemic control, and advice about changes in insulin dosage. Cognitive restructuring techniques also had to address diabetes-related thoughts. The general applicability and cost-effectiveness of this type of approach for the treatment of patients with co-existing eating disorders and diabetes is discussed.